2010
DOI: 10.1186/1476-511x-9-98
|View full text |Cite
|
Sign up to set email alerts
|

The Δ4-desaturation pathway for DHA biosynthesis is operative in the human species: Differences between normal controls and children with the Zellweger syndrome

Abstract: BackgroundDocosahexaenoic acid (DHA, 22:6ω3) is a fundamental component of cell membranes, especially in the brain and retina. In the experimental animal, DHA deficiency leads to suboptimal neurological performance and visual deficiencies. Children with the Zellweger syndrome (ZS) have a profound DHA deficiency and symptoms that can be attributed to their extremely low DHA levels. These children seem to have a metabolic defect in DHA biosynthesis, which has never been totally elucidated. Treatment with DHA eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
(36 reference statements)
0
12
0
Order By: Relevance
“…The cell culture procedure was designed to ensure that culture conditions in vitro are as close as possible to the in-vivo physiological microenvironment of cells. Nevertheless, it has been reported that fatty acid patterns are substantially altered when cell lines are immortalized [45] and in malignant cells [46]. The proportion of polyunsaturated fatty acid in both cases is much lower than in normal cells.…”
Section: Phosphorus Assay Of Major Phospholipid Classesmentioning
confidence: 98%
“…The cell culture procedure was designed to ensure that culture conditions in vitro are as close as possible to the in-vivo physiological microenvironment of cells. Nevertheless, it has been reported that fatty acid patterns are substantially altered when cell lines are immortalized [45] and in malignant cells [46]. The proportion of polyunsaturated fatty acid in both cases is much lower than in normal cells.…”
Section: Phosphorus Assay Of Major Phospholipid Classesmentioning
confidence: 98%
“…Likewise transfection with Thraustochytrium sp. delta-4-desaturase (FAD4) was tested successfully in vitro as a future therapeutic option, although it does not represent the physiological pathway and the practical feasibility of this approach is not clear yet (Martinez et al, 2010).…”
Section: Zellweger Syndromementioning
confidence: 99%
“…Depletion of plasmenyl-ethanolamine and DHA in brain characterizes patients suffering from Zellweger syndrome, leading to serious dysmyelination and multiple neurological abnormalities (Martinez and Mougan, 1999). DHA is an essential fatty acid in nervous tissue and retina, and is therefore implicated in normal brain and retina development, and in cognitive function (Martinez et al, 2010).…”
Section: Biological Propertiesmentioning
confidence: 99%